2013
DOI: 10.3732/apps.1300005
|View full text |Cite
|
Sign up to set email alerts
|

Development of microsatellites for Verbenoxylum reitzii (Verbenaceae), a tree endemic to the Brazilian Atlantic Forest

Abstract: • Premise of the study: Microsatellite markers were developed for Verbenoxylum reitzii (Verbenaceae), a tree endemic to the Brazilian Atlantic Forest, to investigate their usefulness in population genetic studies. The loci were tested for cross-amplification in the related genera Recordia and Duranta.• Methods and Results: Eleven polymorphic microsatellite markers were isolated from an enriched library of V. reitzii and characterized. The primers were tested on 60 individuals from three populations of this spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…PCR amplifications of the 10 SSR loci were performed using previously described protocols (Thode et al, 2013b). The length of the amplified fragment of DNA was measured on a MegaBACE™ 1000 automated sequencer using an ET-ROX 550 size ladder (GE Healthcare).…”
Section: And Microsatellite Genotypingmentioning
confidence: 99%
“…PCR amplifications of the 10 SSR loci were performed using previously described protocols (Thode et al, 2013b). The length of the amplified fragment of DNA was measured on a MegaBACE™ 1000 automated sequencer using an ET-ROX 550 size ladder (GE Healthcare).…”
Section: And Microsatellite Genotypingmentioning
confidence: 99%
“…In a study on Verbenoxylum reitzii (Verbenaceae), an endemic tree of the Brazilian Atlantic Forest, which investigated its usefulness in population genetic studies, SSR markers revealed high polymorphism, acting as a powerful tool for genetic and phylogeographic studies of populations. The marker was effective, providing genetic information for the development of conservation strategies for the species [57][58].…”
Section: Annals Of Reviews and Researchmentioning
confidence: 99%